Analisis Kinerja Satuan Polisi Pamong Praja dalam Menertibkan Pedagang Kaki Lima: Studi Kasus Pasar Inpres Distrik Biak Kota Kabupaten Biak Numfor - Pasang, Nofianto; Fatmawada, Fatmawada; Irawan, Hermanu; Dahlan, Dahlan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this study is to find out how the Municipal Police Force performs in regulating street vendors in Biak Numfor Regency, to determine the factors that influence the performance of the Municipal Police Force in organizing street vendors at the Inpres Market, Biak City District, Biak Numfor Regency. The theory used in this study is the organizational performance theory according to Dwiyanto (2008: 50), which includes productivity, service quality, responsiveness, responsibility, and accountability. The research method used is qualitative research. After the data is collected, it is then reduced and presented, and then a temporary conclusion is drawn about the data related to the issues being researched and analyzed before a final conclusion is made. The performance of the Municipal Police Force in regulating Street Vendors at the Inpres Market, Biak City District, Biak Numfor Regency based on productivity, service quality, and responsiveness indicators is not optimal. Meanwhile, the accountability indicator has been running optimally as evidenced by the Municipal Police Force which has published reports related to accountability reports of the agency to the Local Government. Factors affecting the performance of the Municipal Police Force in regulating Street Vendors at the Inpres Market in Biak are internal and external factors. Internal factors include human resources, facilities and infrastructure, and budget. External factors include political interests. In addition, the lack of socialization to the street vendors regarding local regulations explaining about street vendors, and coordination with stakeholders also affect the performance of the Municipal Police Force in regulating Street Vendors at the Inpres Market in Biak.